The Implementation of Active Learning Strategy of True or False Type in Improving the Learning Outcomes of Grade IX Students in the Subject of Akidah Akhlak at MTs. Al-Qalam Teppo - Arianto, Reza; Darwis; Azis, Ahmad Ridhai (JURNAL SINTAK, 2025)
This study tested the True or False Active Learning strategy in improving the learning outcomes of ninth-grade students at MTs. Al-Qalam Teppo. The objectives of this study were: 1) analyzing learning outcomes before implementing the True or False Active Learning strategy, 2) analyzing learning outcomes after implementing the True or False Active Learning strategy, and 3) examining whether there were differences in learning outcomes before and after implementing the True or False Active Learning strategy. The research method used a quantitative pre-experimental approach with a One Group Pretest-Posttest design. The subjects consisted of 23 ninth-grade B students selected using purposive sampling. The research instrument used a pre-test and post-test, with descriptive and inferential statistical analysis. The results showed an increase in the average score from 46.04 (pre-test) to 72.39 (post-test). Based on the results of the paired-sample t-test, the significance level was 0.001 (<0.05), thus H1 was accepted and H2 was rejected. In conclusion, the True or False type Active Learning strategy can improve learning outcomes in the Aqidah Morals subject.